Deployment of Brassica carinata A. Braun Derived Brassica juncea (L.) Czern. Lines for Improving Heterosis and Water Use Efficiency Under Water Deficit Stress Conditions - Omkar Maharudra Limbalkar (Frontiers Media S.A., 2021)
Among Brassica species, Ethiopian mustard (Brassica carinata A. Braun) is known to tolerate most abiotic stresses, including drought. Drought caused by low and erratic rainfall in semi-arid regions consistently challenges rapeseed mustard productivity. Development of B. carinata-derived lines (CDLs) in Brassica juncea (L.) Czern. nuclear background, carrying genomic segments from B. carinata, are expected to tolerate moisture deficit stress conditions. The present study was, thus, aimed to establish the phenomenon “heterosis” for drought tolerance and water use efficiency by evaluating 105 hybrids developed from intermating 15 CDLs in half diallel fashion. Data on 17 seed yield and yield contributing traits were recorded under two different environments, viz., irrigated and rainfed conditions. Traits under study were found to be governed by both additive and non-additive types of gene action. Average degree of dominance was higher (>2) for yield and yield contributing traits, viz., secondary branches/plant, point to first siliqua on main shoot, total siliquae/plant, 1,000-seed weight, seed yield/plant, biological yield, harvest index, and seed yield/hectare under rainfed conditions, clearly indicating that higher productivity under drought conditions can be realised through the development of hybrids. Out of 15, highly significant general combining ability (GCA) effects for seven CDLs were observed under rainfed condition. Furthermore, nine and six hybrids expressed highly significant specific combining ability (SCA) effects and > 50% heterobeltiosis for yield contributing traits under rainfed and irrigated conditions, respectively. Water use efficiency (WUE) of parental CDLs and hybrids varied from 2.05 to 2.57 kg m–3 under rainfed, while 1.10 to 1.28 kg m–3 under irrigated conditions. Hybrids expressed higher WUE than parental lines under both water regimes. Furthermore, selection indices such as drought tolerance index (DTI) and mean relative performance (MRP) were identified to be efficient in the selection of productive CDLs and hybrids under drought conditions. Nine hybrids, identified as highly productive in the present study, can further be exploited for improving the yield of Indian mustard in drought-prone areas. Usefulness of interspecific hybridisation in the development of B. carinata-derived B. juncea lines for improving heterosis and WUE is, thus, well demonstrated through the present study.